Situation Report: Heavy Rainfall &Floods, Gezira state, Sudan, August, 2013 - Ghebreselasie, Daniel Tekie; Hussein, Salwa Elsanousi; Omer, Sausan; Yousif, Magda Elhadi; Abdalrahman, Samira Hamid (مجلة الجزيرة للعلوم الصحية; مجلد 9 عدد 2 (2013), 2013)
Heavy rainfall &floods are the most common hazards to cause disasters and have led to extensive morbidity and mortality throughout the world. The impact of floods on the human community is related directly to the location and topography of the area, as well as human demographics and characteristics of the built environment. In Sudan heavy rains have fallen since the beginning of August, 2013. Although rains at this time of the year are common, this year they have been heavier than average and had a particularly serious impact. Weeks of heavy rains across Sudan have triggered flash floods, affecting as many as 530,000 people since the beginning of August. Gezira state is also one of the affected areas by this natural disaster. Um-Elgora Locality of Gezira state, which lies east to the Blue Nile, is one of the highly affected areas by of the heavy rainfall disaster. Responses coordinated by University of Gezira were paramount. Faculty of Medicine University of Gezira is pioneered for its innovative community based medical education and community oriented medical practice, which readily participates in responses to emergency health problems of the community. Moreover it cordially collaborates and works closely with MOH and the community of localities. We present here a situational report of heavy rainfall & flash flood in villages of Um- Elgora locality of Gezira state and the responses mainly coordinated by Gezira University.